Capacity utilization under credit constraints: A firm‐level study of Latin American manufacturing. (14th August 2020) - Zhang, Dengjun
Abstract: In developing countries, the credit market usually is underdeveloped. Low access to credit affects firms' production decisions and restrains them from optimizing inputs to achieve the maximum output. This article examines the link between credit constraints and capacity utilization and whether it varies across manufacturing subsectors. The sample consists of 4, 790 private manufacturing firms in six Latin‐American countries. The endogenous switching model is applied to control for endogeneity between credit constraint conditions and capacity utilization and heterogeneity between credit‐constrained and credit‐unconstrained firms. The counterfactual analysis based on the estimation results suggests that constrained firms would have seen an increase of 26.8% capacity utilization had they not been constrained and unconstrained firms a decrease of 23.7% capacity utilization had they been constrained. Credit constraints generally affect medium‐high‐tech firms more severely than low‐tech firms. The counterfactual analysis further reveals that, for credit‐constrained high technology firms, depressed outputs are primarily related to labor productivity rather than capital productivity.